2013
DOI: 10.1016/j.aju.2013.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Different urodynamic patterns in female bladder outlet obstruction: Can urodynamics alone reach the diagnosis?

Abstract: ObjectiveTo define the different urodynamic patterns in female bladder outlet obstruction (BOO) and to assess whether urodynamics alone can be relied on for the diagnosis.Patients and methodsThis prospective study included 60 clinically obstructed women and 27 with stress urinary incontinence as a control group. All patients had pressure-flow studies and were divided into four groups. Group A (control group, 27 patients) and group B (22) had a maximum urinary flow rate (Qmax) of >15 mL/s and a detrusor pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…[ 19 ] There is an agreement that neither pressure-flow data only nor clinical symptoms alone are sufficient for diagnosing BOO in females. In the study by Elmissiry et al .,[ 4 ] two thresholds in accordance with the study of Chassagne et al . [ 11 ] were used and they showed that the best threshold for Qmax and PdetQmax derived from receiver operating characteristic curves to define obstruction in women was 15 mL/s and 30 cmH 2 O, respectively, with a sensitivity of 80% and a specificity of 70%.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…[ 19 ] There is an agreement that neither pressure-flow data only nor clinical symptoms alone are sufficient for diagnosing BOO in females. In the study by Elmissiry et al .,[ 4 ] two thresholds in accordance with the study of Chassagne et al . [ 11 ] were used and they showed that the best threshold for Qmax and PdetQmax derived from receiver operating characteristic curves to define obstruction in women was 15 mL/s and 30 cmH 2 O, respectively, with a sensitivity of 80% and a specificity of 70%.…”
Section: Discussionsupporting
confidence: 83%
“…The first group of patients with voiding symptoms, that is, the clinically obstructed patient can be divided urodynamically into three grades of BOO as mentioned in a study by Elmissiry et al . [ 4 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Incidence has been varied, ranging from 2.7-23%, due to non-uniform definitions. [5] In our study, it measured 31.25% (25/80). Symptoms alone are insufficient in predicting BOO.…”
Section: Discussionmentioning
confidence: 95%
“…For application in the urinary system, hermetic closure should be assured: sudden coughs and involuntary abdominal muscle contractions can generate pressures up to 12 kPa. However, this physiological parameter depends on the patient's anatomical features, therefore a tunable opening pressure (OP) is desirable [20][21][22]. As highlighted below, this can be achieved by making small changes to the valve profile geometry or by slightly changing material stiffness.…”
Section: Introductionmentioning
confidence: 99%